Thermomechanical Properties and Shape‐Memory Behavior of Bisphenol A Diacrylate‐Based Shape‐Memory Polymers. Issue 1 (3rd December 2015) - Santiago, David; De la Flor, Silvia; Ferrando, Francesc; Ramis, Xavier; Sangermano, Marco
Abstract : A series of acrylate‐based shape‐memory materials are synthesized from bisphenol A diacrylate monomers as crosslinking agents. Networks are synthesized by keeping constant the content of bisphenol A‐based crosslinking agent and systematically varying the content ratio of different monofunctional chain builder monomers. The implications of the structure of bisphenol A‐based monomers and the chemical structure and content of monofunctional monomers on thermomechanical properties are discussed. Thermomechanical properties are analyzed using dynamic mechanical analyses and mechanical properties are studied at room temperature and at the onset of the glass transition temperature. Shape‐memory performances under isothermal and transient temperature conditions are also carried out. Tensile tests show excellent values of stress at break up to 45 and 15 MPa at room and high temperature, respectively. The measurements show excellent shape recovery and shape fixity ratios, ≈95% and 97%, respectively. These materials also show very high recovery velocities under transient temperature conditions, up to 24% min −1, and very short recovery times, up to 1.5 s, under isothermal conditions in a water bath. The results confirm that networks synthesized from bisphenol A crosslinkers are promising shape‐memory materials. Abstract : A series of acrylate‐based shape‐memory materials are synthesized from bisphenol A diacrylate monomers as crosslinking agents. The structure of the bisphenol‐A based monomers and the different content of monofunctional monomers have important implication on thermomechanical properties. Results show excellent mechanical properties, high shape recovery, and shape fixity ratios as well as fast recovery velocities under isothermal and transient temperature conditions.